Bronchoscopy and molecular diagnostic techniques to identify superimposed infections in COVID-19-associated ARDS: a case series from Ecuador during the second wave - Briones Claudett, Killen Harold; Briones-Claudett, Mónica H.; Murillo Vasconez, Roger; Benitez Sólis, Jaime G.; Briones Zamora, Killen H.; Freire, Amado X.; Barberan-Torres, Pedro; Grunauer, Michelle (Frontiers in Medicine, 2024)
Abstract: Introduction: COVID-19-associated acute respiratory distress syndrome (CARDS) poses significant challenges in resource-limited settings. This case series explores the role of bronchoscopy and molecular techniques in identifying superimposed infections in CARDS patients during the second wave of the pandemic in Ecuador. Methods: Nine critically ill CARDS patients underwent bronchoscopy and molecular testing to detect co-infections and superinfections. Clinical presentations, diagnostic findings, and outcomes were analyzed. Results: Bronchoscopy and molecular techniques identified a range of secondary infections, including multidrug-resistant pathogens such as Acinetobacter baumannii and Klebsiella pneumoniae. The case series highlights the complexities of managing severe COVID-19 cases in resource-constrained environments. Discussion: Early identification of microorganisms using PCR methods allows for rapid and accurate diagnosis, facilitating targeted management of critically ill CARDS patients. The study underscores the importance of advanced diagnostic tools and adaptable strategies in pandemic situations, particularly in low-resource settings.